2017
DOI: 10.1016/j.ebiom.2017.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Public Health HIV Interventions: A Qualitative Meta-Synthesis and Systematic Review of Studies to Improve Linkage to Care, Adherence, and Retention

Abstract: Although HIV services are expanding, few have reached the scale necessary to support universal viral suppression of individuals living with HIV. The purpose of this systematic review was to summarize the qualitative evidence evaluating public health HIV interventions to enhance linkage to care, antiretroviral drug (ARV) adherence, and retention in care. We searched 19 databases without language restrictions. The review collated data from three separate qualitative evidence reviews addressing each of the three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 52 publications
3
27
0
Order By: Relevance
“…The 6-month interval did not incentivize selling or sharing. Although the literature indicates that financial stress can influence ART adherence due to lack of money for transport to clinic or inability to step away from incomegenerating activities for refill visits, 2,18,21 there is scarce published evidence of selling ART for economic improvement. As clients and providers mentioned, there is a limited market for selling ART because medications are provided for free in most settings.…”
Section: Discussionmentioning
confidence: 99%
“…The 6-month interval did not incentivize selling or sharing. Although the literature indicates that financial stress can influence ART adherence due to lack of money for transport to clinic or inability to step away from incomegenerating activities for refill visits, 2,18,21 there is scarce published evidence of selling ART for economic improvement. As clients and providers mentioned, there is a limited market for selling ART because medications are provided for free in most settings.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review focused on adolescents, given high attrition in this group, identified education and counseling, financial incentives, increasing clinic accessibility, and adolescent-specific services as promising to improve linkage and retention [ 39 ]. Finally, a systematic review of studies to increase linkage, adherence, and retention noted key themes including poverty, food insecurity, transportation and housing constraints, and unmet mental health needs as factors limiting the success of public health HIV interventions [ 40 ]. To maximize the impact of health systems strengthening activities, all of these factors must be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review examining various ART adherence interventions have concluded that behavioral interventions producing a positive impact in one setting may not translate to other populations because of differences in economic, social, and behavioral barriers to adherence [ 33 ]. Such barriers including poverty and mental health comorbidities commonly co-exist in various contexts, and addressing these issues through respective integrative services alongside public health HIV interventions may increase implementation success of the latter [ 34 ].…”
Section: Discussionmentioning
confidence: 99%